2016
DOI: 10.1007/s11065-016-9330-4
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Impact of Cognitive Interventions in Mild Cognitive Impairment: a Systematic Review and Meta-Analysis

Abstract: Cognitive interventions in Mild Cognitive Impairment (MCI) seek to ameliorate cognitive symptoms in the condition. Cognitive interventions may or may not generalize beyond cognitive outcomes to everyday life. This systematic review and meta-analysis sought to assess the effect of cognitive interventions compared to a control group in MCI on generalizability outcome measures [activities of daily living (ADLs), mood, quality of life (QOL), and metacognition] rather than cognitive outcomes alone. PRISMA guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
107
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(129 citation statements)
references
References 125 publications
(255 reference statements)
5
107
0
7
Order By: Relevance
“…Three reviews reported meta-analytical results for both CT and CS (Folkerts et al, 2017;Huntley et al, 2015;Kurz et al, 2011). Six were classified as mixed COTs (Chandler et al, 2016;Lee et al, 2019;P. Leung et al, 2017;Rogers et al, 2018;Sherman et al, 2017;Yang et al, 2018), one of which focused specifically on COTs with caregiver involvement (P. Leung et al, 2017).…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three reviews reported meta-analytical results for both CT and CS (Folkerts et al, 2017;Huntley et al, 2015;Kurz et al, 2011). Six were classified as mixed COTs (Chandler et al, 2016;Lee et al, 2019;P. Leung et al, 2017;Rogers et al, 2018;Sherman et al, 2017;Yang et al, 2018), one of which focused specifically on COTs with caregiver involvement (P. Leung et al, 2017).…”
Section: Interventionsmentioning
confidence: 99%
“…three in MCI (mixed COTs:Chandler et al, 2016; CT: Gates, Vernooij, et al, 2019;Hill et al, 2017), four in dementia (CT:Bahar-Fuchs et al, 2019;Hill et al, 2017; CS: Kim et al, 2017; Woods et al, 2012), one in PD (CT: I. H Leung et al, 2015),. two in stroke (CT: dasNair et al, 2016;Loetscher & Lincoln, 2013) and one in mixed MCI and dementia (CT:Hoefler, 2016).…”
mentioning
confidence: 99%
“…A few small‐scale cognitive training studies have reported positive findings in persons with MCI, and a number of reviews have concluded that it is a potentially effective method for improving cognition and postponing cognitive decline, but many studies rely on a waitlist rather than an active control as a condition of reference, do not provide information on long‐term maintenance of cognitive improvements, do not report data on mood and quality of life, and lack information on whether the learned strategies transfer to real life. These issues limit our ability to conclude that cognitive training improves cognition in MCI and to recommend its use as a strategy to reduce cognitive decline …”
mentioning
confidence: 99%
“…There is growing recognition, however, that these may not be the most suitable outcomes, and that it may be more important to consider whether, and how, a memory intervention impacts daily life. Besides measures of everyday function, impact on daily life encompasses mood, quality of life, and metacognitive outcomes (i.e., how one thinks or feels about cognitive processes) (Chandler, Parks, Marsiske, Rotblatt, & Smith, ). Moreover, improved memory self‐efficacy—not change in memory test performance—is one of the most important outcomes reported by participants of memory interventions (Barrios et al, ).…”
Section: Outcome Measurementmentioning
confidence: 99%